Development of Vocational Skills for Mild Mentally Retarded Children on Making Bags from Batik Cloth at the SMALB Level - Ningtyas, Teguh Denada Diah Ayu; Budiyanto, Budiyanto; Andajani, Sri Joeda (Angstrom Centre of Education, 2022)
Learning the vocational skills of children with mild mental retardation today has encountered many difficulties which resulted in the limitations of children in mastering the vocational skills of making bags from batik cloth. This study aims to produce a product for developing vocational skills learning for mild mentally retarded children towards making bags from batik cloth at the SMALB level. This research method uses Research and Development (R&D) research to produce a certain product, and tests the effectiveness of the product to perfect a product that is in accordance with the references and criteria of the product made so as to produce a new product through various stages, validation, and testing that includes a learning video tutorial that makes it easier for mild mentally retarded children to understand and develop vocational skills in making bags from batik cloth. The conclusion of this study is that with the development of vocational skills learning for mild mentally retarded children, it is hoped that mild mentally retarded children at the SMALB level have vocational skills to make bags from batik cloth which can be used as life skills to prepare them for entering the workforce after graduation and these vocational skills need to be trained so that the vocational skills of mild mentally retarded children can develop optimally. The results of the expert validation test are in the form of learning video tutorials and bags from batik cloth which are categorized as valid and effective. The conclusion of this study is that with the development of vocational skills learning for mild mentally retarded children, it is hoped that mild mentally retarded children at the SMALB level have vocational skills to make bags from batik cloth which can be used as life skills to prepare them for entering the workforce after graduation and these vocational skills need to be trained so that the vocational skills of mild mentally retarded children can develop optimally. The results of the expert validation test are in the form of learning video tutorials and bags from batik cloth which are categorized as valid and effective. The conclusion of this study is that with the development of vocational skills learning for mild mentally retarded children, it is hoped that mild mentally retarded children at the SMALB level have vocational skills to make bags from batik cloth which can be used as life skills to prepare them for entering